Entrepreneurial Orientation and Product Innovation Performance of MSMEs in West Java: Foresight Capabilities as a Mediating Variable - Vigory Gloriman Manalu; Faishal Rahimi; Ilham Akbar (Khazanah Sosial, 2023)
MSMEs have become the foundation for growth in various countries, including Indonesia. Especially in West Java, MSMEs play an essential role in absorbing labour. However, MSMEs in West Java face an uncertain business environment and difficulties in creating products that suit market needs. This research will use the Resource Based View (RBV) and Dynamic Capability View (DCV) theories. This research examines the influence of entrepreneurial orientation on the innovation performance of MSMEs by using foresight capabilities as a mediating variable. 245 MSMEs were collected as respondents to fill out the survey questionnaire. The MSMEs used in this research are from West Java, with the main characteristics of operating for more than one year and developing new products for at least two years. Structural equation modeling (SEM) was used to test the research framework. It was found that entrepreneurial orientation can influence the innovation performance of MSMEs positively and significantly. The influence of foresight capabilities on MSME product innovation performance has a positive effect. The mediating effect of foresight capabilities on the relationship between entrepreneurial orientation and product innovation performance was partially mediated. MSMEs that behave more entrepreneurially benefit from being more proactive, innovative, and risk-taking in an uncertain market environment. Product innovation can be achieved through a good understanding of entrepreneurial orientation mediated by an understanding of Foresight to process information for future decisions. Finally, managerial and theoretical implications and future research are presented.